Application Of Jigsaw Method Of Reading In Improving Learning Outcomes Indonesian Student Class Iv Elementary Instruction 12/79 Wollangi Barebbo District Of Bone Regency - Abd Hafid; Hasbi R; Satriani DH (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2017)
The problem in this research is the low learning outcomes Indonesian students fourth grade Instruction 12/79 Wollangi Barebbo District of Bone regency. The formulation of the problem in this research is how the application of the method Jigsaw read in improving learning outcomes Indonesian students fourth grade Inpres12 / 79 Wollangi Barebbo District Subdistrict Bone? The purpose of this study is to describe the application of Jigsaw reading method in improving learning outcomes Indonesian on fourth grade students Instruction 12/79 Wollangi Barebbo District of Bone regency. This research approach is descriptive qualitative approach to the type of classroom action research cycle repeated / cyclic that includes planning, implementation, observation and reflection. The focus of this research is the application of methods Jigsaw reading and learning outcomes Indonesian. Subjects were students in fourth grade Instruction 12/79 Wollangi Barebbo District of Bone regency. Research data collection techniques are tests and observation. Data analysis techniques in the study of data reduction, data presentation, draw conclusions and verification. The results showed an increase in student learning outcomes of the first cycle with enough categories to increase to both categories at the second cycle. The conclusion of the research is the application of methods Jigsaw reading can improve learning outcomes Indonesian students fourth grade Instruction 12/79 Wollangi Barebbo District of Bone regency.